The Importance of Morphometric Measurements of Adult Human Dry Hip Bone in Acetabular Reconstruction - Memduha Gülhal Bozkır; A. Kürşad Açıkgöz (Journal of Contemporary Medicine, 2022)
Objective: The aim of this study was to obtain morphometric measurements of adult human hip bones, examine the relationship among these measurement parameters, and develop regression equations to estimate the acetabular dimensions for acetabular reconstruction Material and Method: Seventy-eight (39 right and 39 left) dry hip bones of unknown age and gender located in the laboratory of Çukurova University Faculty of Medicine, Department of Anatomy, were included in the study. Eleven hip bones with fractures, deterioration, deformities, and defects that would affect the measurements were excluded from the study. In our study, 14 morphometric measurements of hip bones were obtained. IBM SPSS program was used for statistical analysis. Results: Single and multiple regression equations were developed from the hip bone morphometric measurements for the estimation of the morphometric measurements of the acetabulum. The standard error of estimate (SEE) values ranged from ±1.818 mm to ±3.546 mm in single regression equations, and between ±1.633 mm and ±2.107 mm in multiple regression equations. A lower SEE value was obtained in multiple regression equations than in single regression equations. Conclusion: The regression equations developed in this study will allow us to obtain personalized measurements, which will aid clinicians in the correct and safe placement of the implant in hip replacement surgeries as well as in the prevention of complications with the use of appropriate prostheses.